Apoiando a construção de gráficos por usuários inexperientes através de recomendações - Sousa, Taissa Abdalla Filgueiras de; Barbosa, Simone Diniz Junqueira (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2012)
Visualization research emphasizes the need for systems that assist in decision-making and visual analysis. This paper outlines a recommender system that supports the interactive construction of charts using statistical data. Based on a sequence of simple user interactions, the interface automatically generates an elementary view. This process yields knowledge in an implicit manner, which enables the system to analyze the selected dataset, suggest visualization options and provide guidelines for selecting the most appropriate representation for a given problem.